Review of Jennifer Bowering Delisle, The Newfoundland diaspora: mapping the literature of out-migration - Monk, Craig (My University, 2013)
As Jennifer Bowering Delisle argues, out-migration from Newfoundland is both a preoccupation for many of its writers and a condition under which some of their literary output is produced. Because leaving the province is such a universal phenomenon--indeed, the author observes that it is "often expected or considered inevitable" (3)--out-migration serves as more than simply a thematic concern. It forms the signature trope that, when combined with an expressed desire to return "home," defines the shared experience central to Newfoundland literature and provides Delisle with the foundation from which she seeks to theorize diaspora in an Atlantic Canadian context. To this point, by her reckoning, the concept has been applied too loosely to the Newfoundland experience, and so the author connects diaspora purposefully to five features of out-migration. In large measure, Newfoundlanders "abroad" experience a painful separation, an unbroken connection to the island, and a sense of marginalization in their new homes. In response, they form communities of the like-minded and together regard Newfoundland in neo-national terms (10). While these commonalities are essential to her understanding of diaspora, Delisle seems most troubled by the application of this last feature. Is Newfoundland in its literature depicted as a region, a province, or a nation? Ultimately, the author seems to understand this figurative Newfoundland as a nation, one that transcends its nebulous status before confederation to strengthen its place within Canada and sharpen the features of its creative heritage.
Keywords: literary criticism